Manicômios, pseudo(auto) biografias e narradores pouco confiáveis: de Machado de Assis a Carlos Sussekind - Markus Lasch (Universidade de Brasília, 2009)
This article discusses questions of subject and subjectivity in the works of Machado de Assis and Carlos Sussekind. It focuses on the "dialectic of the writings of the self", relating three texts by Machado de Assis -O Alienista, Esaú e Jacóand Memorial de Aires- to the novels Armadilha para Lamartine and O autor mente muito, by Carlos Sussekind, regarding the instances of author and narrator, and concerning the mental hospital as "house of power".